Electrochemical properties of La1.5Pr0.5Ni0.95−xCuxAl0.05O4+δ Ruddlesden-Popper phase as cathodes for intermediate-temperature solid oxide fuel cells. (November 2020) - Zhou, Qingjun; Zhang, Ting; Zhao, Chen; Qu, Liangwu; He, Yong; Wei, Tong; Tong, Xiaoqiang
Graphical abstract: Highlights: Cu and Al co-doped La1.5 Pr0.5 NiO4+ δ are potential cathode materials of IT-SOFCs. The obtained cathodes exhibited excellent phase stability at high temperatures. ASR of La1.5 Pr0.5 Ni0.85 Cu0.1 Al0.05 O4+ δ is 0.042 Ω cm 2 at 800 °C. Abstract: The Ruddlesden-Popper materials La1.5 Pr0.5 Ni0.95− x Cu x Al0.05 O4+ δ ( x = 0, 0.1, 0.25, 0.5, 0.75, 0.95), La1.5 Pr0.5 NiO4+ δ, and La1.5 Pr0.5 CuO4+ δ have been synthesized by the sol-gel method as cathode materials on the SDC (Sm0.2 Ce0.8 O1.9 ) electrolyte for intermediate-temperature solid oxide fuel cells (IT-SOFCs). The cathode materials sintered at 700 and 800 °C for 72 h, also showing good phase stability. The maximum conductivity of this series reached approximately 50 S cm −1 at 350 °C with x = 0.25. The lowest area-specific resistance (ASR) of the cathode measured on the SDC was 0.04 Ω cm 2 at 800 °C with x = 0.1. The maximum power density of the SDC-supported single-cell reached 530 mW cm −2 at 800 °C with x = 0.1. Among all of the samples, La1.5 Pr0.5 Ni0.85 Cu0.1 Al0.05 O4+ δ exhibited excellent electrochemical performance, making it a promising candidate cathode material for IT-SOFCs.